The Safety and Feasibility of Image-Guided BrainPath-Mediated Transsulcul Hematoma Evacuation: A Multicenter Study. Issue 4 (19th January 2017) - Labib, Mohamed A.; Shah, Mitesh; Kassam, Amin B.; Young, Ronald; Zucker, Lloyd; Maioriello, Anthony; Britz, Gavin; Agbi, Charles; Day, JD; Gallia, Gary; Kerr, Robert; Pradilla, Gustavo; et al.
Abstract: BACKGROUND: Subcortical injury resulting from conventional surgical management of intracranial hemorrhage may counteract the potential benefits of hematoma evacuation. OBJECTIVE: To evaluate the safety and potential benefits of a novel, minimally invasive approach for clot evacuation in a multicenter study. METHODS: The integrated approach incorporates 5 competencies: (1) image interpretation and trajectory planning, (2) dynamic navigation, (3) atraumatic access system (BrainPath, NICO Corp, Indianapolis, Indiana), (4) extracorporeal optics, and (5) automated atraumatic resection. Twelve neurosurgeons from 11 centers were trained to use this approach through a continuing medical education–accredited course. Demographical, clinical, and radiological data of patients treated over 2 years were analyzed retrospectively. RESULTS: Thirty-nine consecutive patients were identified. The median Glasgow Coma Scale (GCS) score at presentation was 10 (range, 5-15). The thalamus/basal ganglion regions were involved in 46% of the cases. The median hematoma volume and depth were 36 mL (interquartile range [IQR], 27-65 mL) and 1.4 cm (IQR, 0.3-2.9 cm), respectively. The median time from ictus to surgery was 24.5 hours (IQR, 16-66 hours). The degree of hematoma evacuation was ≥90%, 75% to 89%, and 50% to 74% in 72%, 23%, and 5.0% of the patients, respectively. The median GCS score at discharge was 14 (range, 8-15). The improvement in GCS score was statistically significant ( P < .001). Modified Rankin Scale data were available for 35 patients. Fifty-two percent of those patients had a modified Rankin Scale score of ≤2. There were no mortalities. CONCLUSION: The approach was safely performed in all patients with a relatively high rate of clot evacuation and functional independence.